Ibn Daud’s universal history - Vehlow, Katja (Anales del Seminario de Historia de la Filosofía, 2023)
In his universal history, Dorot ‘Olam, written in four brief interdependent texts, Ibn Daud unfolds a comprehensive vision of history. Dorot ‘Olam is a literary product of the twelfth-century political, cultural, and historiographical conditions in his hometown Toledo, and the Iberian Peninsula at large. Merging contemporary Jewish and rabbinic concerns with Arabic Islamic philosophical thought and Christian historiography, Ibn Daud’s historical writings were eagerly embraced and read by Jews and especially early modern Christians in Europe and North America.